1997
DOI: 10.1093/ndt/12.8.1615
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow-up of kidney donors: a longitudinal study

Abstract: This study demonstrates that the function of the solitary kidney is not adversely affected by prolonged compensatory hyperfiltration, although there appears to be an increased prevalence of microalbuminuria and hypertension. Regular follow-up of kidney donors is recommended in order to manage their complications effectively and to detect hypertension and or renal impairment early in those who may develop it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
74
0
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(78 citation statements)
references
References 0 publications
2
74
0
2
Order By: Relevance
“…In a rat model of oligonephronia induced in utero by gentamicin and using descriptive histological techniques only, mesangial lesions and glomerular sclerosis were more common than in control animals at 24 months [31]. A parallel may be drawn with renal transplant donors, where longitudinal studies have shown no adverse effects in the early years after nephrectomy [32] but an increased prevalence of microalbuminuria and hypertension after 12-31 years [33].…”
Section: Discussionmentioning
confidence: 96%
“…In a rat model of oligonephronia induced in utero by gentamicin and using descriptive histological techniques only, mesangial lesions and glomerular sclerosis were more common than in control animals at 24 months [31]. A parallel may be drawn with renal transplant donors, where longitudinal studies have shown no adverse effects in the early years after nephrectomy [32] but an increased prevalence of microalbuminuria and hypertension after 12-31 years [33].…”
Section: Discussionmentioning
confidence: 96%
“…Studies that have compared early with late postdonation function have found no difference in mean function in the sample of donors (49,50). In fact, a study by Saran et al (49), which compared 51 Cr EDTA early postdonation and then 10 yr later, found that the mean GFR had actually improved slightly at a follow-up of 20 yr.…”
Section: Renal Failurementioning
confidence: 95%
“…A longitudinal study over 10 years did show an increased prevalence of hypertension in donors when compared with age/sex-matched data from epidemiological studies of the general population (both in the UK and the US). 30 The prevalence of hypertension was 36% at an initial visit 1-21 years after donation, increasing to 75% after 10 years. This effect was especially strong in those donating over the age of 55 years.…”
Section: Risk Of Hypertension After Kidney Donationmentioning
confidence: 97%
“…28,29 Long-term longitudinal studies comparing early and late post-donation GFR have found no evidence of a further decline in mean function over periods of between 10 and 30 years. 30 In a meta-analysis of 48 cross-sectional studies involving over 3000 donors and 1703 controls, uninephrectomy was associated with a reduction in GFR of 17.1 ml min À1 per 1.73 m 2 (95% CI À20.2 to À14.0 ml min À1 per 1.73 m 2 ) that tended to improve slightly with each 10 years of follow-up. 31 These findings are difficult to interpret as GFR was measured by a variety of methods, including creatinine clearance by timed collection and estimated values derived from serum creatinine concentration, both of which are known to be inaccurate particularly at the modestly subnormal GFR levels expected after donation.…”
Section: Renal Function After Kidney Donationmentioning
confidence: 99%